PERTUMBUHAN PENDUDUK, INFLASI DAN KORUPSI: ANALISIS EMPIRIS ENVIRONMENTAL KUZNETS CURVE (EKC) DI KAWASAN ASEAN PERIODE 2002-2016 - Trianto, Muhammad Fajri Setia; Purwanti, Evi Yulia (JURNAL DINAMIKA EKONOMI PEMBANGUNAN, 2018)
The economy that continues to grow has the impact of environmental damage. This study aims to prove empirically the Environmental Kuznets Curve (EKC) hypothesis by analyzing the relationship of economic growth with environmental damage as measured by GDP per capita, and CO2 emissions. The data used are secondary data in the form of data on GDP per capita, CO2 emissions, population growth, inflation, and control of corruption in 10 countries in the ASEAN region in 2002-2016. Data analysis using the Fixed Effect model. The results show that there is a relationship between economic growth and environmental damage that forms an inverted U curve. Economic growth will initially have a positive effect on environmental damage so that at a point of economic growth negatively affects environmental damage. By adding control variables: population growth, inflation and corruption, inflation and corruption positively impact environmental damage, while population negatively affect environmental damage.